Biophysical Differences between Chronic Myelogenous Leukemic Quiescent and Proliferating Stem/Progenitor Cells - Guz, Nataliia V. (Nanomedicine, 2016)
The treatment of chronic myeloid leukemia (CML), a clonal myeloproliferative disorder has improved recently, but most patients have not yet been cured. Some patients develop resistance to the available tyrosine kinase treatments. Persistence of residual quiescent CML stem cells (LSC) that later resume proliferation is another common cause of recurrence or relapse of CML. Eradication of quiescent LSCs is a promising approach to prevent recurrence of CML. Here we report on new biophysical differences between quiescent and proliferating CD34+ LSCs, and speculate how this information could be of use to eradicate quiescent LSCs. Using AFM measurements on cells collected from four untreated CML patients, substantial differences are observed between quiescent and proliferating cells in the elastic modulus, pericellular brush length and its grafting density at the single cell level. The higher pericellular brush densities of quiescent LSCs are common for all samples. The significance of these observations is discussed.